Relationship between average and high-intensity power during a professional men`s road cycling race - Martin, D.; McLean, B.; Ebert, T.; Gardner, A.; Lee, H.; Lawton, E.; Ricketson, J.; Stephens, B. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
Because of drafting, average power output can vary greatly between cyclists finishing a race with similar times. We hypothesized that those cyclists producing the highest average power during a 130-145 km race would generally be more fatigued and therefore engage in less high-intensity cycling. From 1999-2003 22 AIS male road cycling scholarship holders (21±1.5 yrs; 74.3±5.2 ml.kg-1.min-1 VO2pk) raced in the "Tour Down Under" with SRM power meters attached to their bicycles. Power data from Stage 2 (n=27) were analysed because this stage was held over similar terrain every year (3.5-4.1 hours, climbs <400m, light wind, 28-34 C). Power data were collected every second (1Hz) during competition and then analysed using custom-built software. In contrast to our expectations, weak positive correlations were observed between average race power (190±35 W, 2.7±0.4 W.kg-1) and time spent >12 W.kg-1 (r=.38). Average race power also showed weak but positive correlations with the maximum mean power sustained for 5 sec, up to 60 sec: MMP5s (r=.46), MMP15s (r=.44), MMP30s (r=.38) and MMP60s (r=.54). The only negative correlation with average race power was time spent at 0 power (r=-.67). The strongest correlations with average race power were for time spent between 4-6 W.kg-1 (r=.81) and 6-8 W.kg-1 (r=.87). In summary, during a ~3.75 hr professional road race over rolling terrain, cyclists that produce the highest average power spend less time resting (0 W), spend more time at high power output (>12 W.kg-1) and tend to generate higher peak power for sprints lasting between 5-60 seconds.